Eribulin versus dacarbazine in previously treated patients with advanced liposarcoma or leiomyosarcoma: a randomised, open-label, multicentre, phase 3 trial. Issue 10028 (16th April 2016) - Schöffski, Patrick; Chawla, Sant; Maki, Robert G; Italiano, Antoine; Gelderblom, Hans; Choy, Edwin; Grignani, Giovanni; Camargo, Veridiana; Bauer, Sebastian; Rha, Sun Young; Blay, Jean-Yves; Hohenberger, Peter; et al.
Summary: Background: A non-randomised, phase 2 study showed activity and tolerability of eribulin in advanced or metastatic soft-tissue sarcoma. In this phase 3 study, we aimed to compare overall survival in patients with advanced or metastatic soft-tissue sarcoma who received eribulin with that in patients who received dacarbazine (an active control). Methods: We did this randomised, open-label, phase 3 study across 110 study sites in 22 countries. We enrolled patients aged 18 years or older with intermediate-grade or high-grade advanced liposarcoma or leiomyosarcoma who had received at least two previous systemic regimens for advanced disease (including an anthracycline). Using an interactive voice and web response system, an independent statistician randomly assigned (1:1) patients to receive eribulin mesilate (1·4 mg/m 2 intravenously on days 1 and 8) or dacarbazine (850 mg/m 2, 1000 mg/m 2, or 1200 mg/m 2 [dose dependent on centre and clinician] intravenously on day 1) every 21 days until disease progression. Randomisation was stratified by disease type, geographical region, and number of previous regimens for advanced soft-tissue sarcoma and in blocks of six. Patients and investigators were not masked to treatment assignment. The primary endpoint was overall survival in the intention-to-treat population. The study is registered withClinicalTrials.gov, numberNCT01327885, and is closed to recruitment, but treatment and follow-up continue. Findings: Between March 10, 2011 and May 22, 2013, we randomly assigned patients to eribulin (n=228) or dacarbazine (n=224). Overall survival was significantly improved in patients assigned to eribulin compared with those assigned to dacarbazine (median 13·5 months [95% CI 10·9–15·6] vs 11·5 months [9·6–13·0]; hazard ratio 0·77 [95% CI 0·62–0·95]; p=0·0169). Treatment-emergent adverse events occurred in 224 (99%) of 226 patients who received eribulin and 218 (97%) of 224 who received dacarbazine. Grade 3 or higher adverse events were more common in patients who received eribulin (152 [67%]) than in those who received dacarbazine (126 [56%]), as were deaths (10 [4%] vs 3 [1%]); one death (in the eribulin group) was considered treatment-related by the investigators. Interpretation: Overall survival was improved in patients assigned to eribulin compared with those assigned to an active control, suggesting that eribulin could be a treatment option for advanced soft-tissue sarcoma. Funding: Eisai.